THE TEXTUAL ROLE OF REPETITION IN THE TRANSLATION OF POLISH AND HUNGARIAN LEGAL TEXTS - KACZMAREK, Karolina (Comparative Legilinguistics, 2009)
This article presents research on written legal texts with a focus on the cohesion of such texts by analyzing the function of lexical repetition. The author indicates the possibility of using Hoey and Károly’s method of researching repetition patterns in texts in the process of translating Polish and Hungarian legal texts. In this analysis Polish, and Hungarian contract texts serve as a search base. Because contracts in both languages are structured into similar units, so called clauses, the author chose it for a base category of analysis. The author used three structures to search for lexical repetitions: intrasentential, intersentential and discourse structure. Because of the specific genre, contract clauses were used for analysis instead of popular linguistic units such as the sentence. Therefore, the discussion here concerns intra-clausulal, inter-clausulal or legal discourse structures. The author states that the number and quality of repetition in Polish und Hungarian contracts is comparable. However, the number of lexical repetition appear to be smaller in Hungarian texts.